2022
DOI: 10.24912/ja.v26i2.934
|View full text |Cite
|
Sign up to set email alerts
|

Testing The Determinants Of Corporate Reputation And Their Impact On Market Valuation

Abstract: This study examines model of the determinants of corporate reputation, namely managerial ability and corporate social performance and their impact on market valuation. Theoretical model is built based on Resource-based theory and signaling theory. Population of this study are all companies listed on the Indonesia Stock Exchange in 2017 – 2020. The results of this study indicate that there is an influence between managerial ability and corporate social performance on corporate reputation. This study also finds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The drivers of corporate reputation explored by Ghuslan et al (2021) demonstrate that effective corporate reputation and the quality of both environmental and social reporting have a positive influence on corporate reputation. Similarly, Limbunan and Daromes (2022) found that managerial and corporate social performance influence corporate reputation of companies listed on stock exchange. On the contrary, the existing literature demonstrates that corporate reputation positively drives word of mouth, customer trust and satisfaction (Fatmawati and Fauzan 2021;Hasan and Hossain 2021).…”
Section: Accidents In Constructionmentioning
confidence: 96%
“…The drivers of corporate reputation explored by Ghuslan et al (2021) demonstrate that effective corporate reputation and the quality of both environmental and social reporting have a positive influence on corporate reputation. Similarly, Limbunan and Daromes (2022) found that managerial and corporate social performance influence corporate reputation of companies listed on stock exchange. On the contrary, the existing literature demonstrates that corporate reputation positively drives word of mouth, customer trust and satisfaction (Fatmawati and Fauzan 2021;Hasan and Hossain 2021).…”
Section: Accidents In Constructionmentioning
confidence: 96%